BUILDING MULTICULTURAL CHARACTERS BASED ON PESANTREN VALUES - Miftahus Salam (International Journal Education Multicultural of Islamic Society, 2021)
Pesantren has long historical source in Indonesia as an educational institution. The adaptive nature of Pesantren and accepting students from various realities leading up to be one of education icon. Pesantren Al Hasani Al Latifi, which is more familiarly known as Pesantren Kauman Bondowoso, is an Islamic boarding school with a multicultural character. The multicultural reality at the Kauman Islamic Boarding School are carried out internally for Pesantren residents, as well as for the people of Kauman Village in general. This article intends to discuss the problem of building a multicultural character based on the values of the Pesantren in Kauman Islamic boarding school Bondowoso.This research is qualitative and the type of case study because of the characteristics and paradigm of Kauman Islamic Boarding School. Researcher as instruments as well as data collectors will carry out observations, interviews, and document retrieval. Data obtained in three ways, namely interviews, observation, and documentation. Data analysis in this study, data analysis was carried out since data collection as a whole and was checked over.The results of the study state a multicultural character with four indicators, that is tolerance, democracy, equality, and justice, reinforced by the values of the Pesantren, Pancabakti. It contains devotion to Allah and His Messenger, Devotion to Religion, Devotion to Teachers, Devotion to Parents, Devotion to Society, Nation, and State. The multicultural character is in synergy with the Pesantren Pancabakti is the main asset in building a space for students' awareness of multicultural characters. Second, understanding the multicultural character means strengthening the emotional sensitivity of Santri regarding indicators of multicultural character and also Islamic boarding school service. Indicators of multicultural character in Kauman Islamic Boarding School, which are synergized with the Islamic Boarding School Pancabakti, make the spectrum of multicultural characters broader and have a religious dimension. Third, multicultural character-based actions carried out by caregivers and Ustadz, are efforts to combine the areas of awareness and understanding of the Santri to accustom students to acting according to multicultural characters. Building multicultural character-based attitude action is given by exemplary in the form of mutual respect, mutual respect, and giving the same treatment regardless of the background of the students. Keywords: Character, Multicultural, Islamic Boarding School Values.